Influence of in-ovo and after hatching treatment with inorganic selenium on productive performance, some hormones and antioxidant status of broiler - Rahawi, Ghadeer AbdAlMonem Mohammed; AbdulMajeed, Abdullah Fathi; AbdulRhaman, Saeeb Younis (Journal of agricultural, environmental and veterinary sciences, 2022)
The current study aimed to evaluate the effects of inorganic selenium (sodium selenite) added to the drinking water of hatched chicks from eggs injected with it on productive performance, antioxidant status, and some hormonal parameters. 216 unsexed one-day-old broiler chicks were distributed into 6 groups (3 replicates, 12 birds/replicate) till 42 days of age, as follows: The first (1st) and second (2nd) groups: hatched chicks came from non-injected eggs without any substance. The third (3rd) and fourth (4th) groups: hatched chicks came from eggs injected with deionized water (0.2 ml/egg) in the chorioallantoic sac, while the fifth (5th) and sixth (6th) groups: hatched chicks came from eggs injected with 0.02 mg sodium selenite/egg in the chorioallantoic sac. Chicks of the 1st, 3rd, and 5th groups were given tap water, while chicks of the other groups were given drinking water supplemented with 0.3 mg sodium selenite/L. Inorganic selenium significantly improved the initial and final body weight, weight gain, feed conversion ratio, and significantly reduced the feed consumption at 35 and 42 days of age. It also enhanced vitality percentage, productive index, and reduced mortality percentage, and it was significant (P≤0.05) at 42 days of age. On the other hand, in-ovo injection with sodium selenite reduced malondialdehyde and corticosterone values, while total antioxidant capacity and leptin increased, and continuing adding it with drinking water led to a significant decrease in malondialdehyde while leptin and thyroxine values significantly increased. In conclusion, the in-ovo injection with sodium selenite and continuous treatment with it after hatching improve the antioxidant status and productive performance of the broiler, and it can be recommended to use sodium selenite in early egg nutrition during incubation period and its supplementation with drinking water of chicks after hatching.
Keywords: Antioxidant; Broiler; In-ovo nutrition; Leptin; Sodium selenite; Productive performance; Thyroid hormones